2017
DOI: 10.1080/13880209.2016.1277766
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of 2-angeloyl ent -dihydrotucumanoic acid

Abstract: Context:Gymnosperma glutinosum (Spreng.) Less. (Asteraceae) is a bush used for the empirical treatment of pain, fever, and cancer. An ent-neo-clerodane diterpene (2-angeloyl ent-dihydrotumanoic acid; ADTA) was isolated from G. glutinosum.Objective: This study evaluates the cytotoxic, anti-inflammatory, and antinociceptive effects of ADTA.Materials and methods: The cytotoxic effects of ADTA (1–350 μM) were evaluated using the MTT assay with human tumorigenic (SW-620, MDA-MB231, SKLU1, SiHa, and PC-3), and non-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Most of the compounds isolated from G. glutinosum are methoxylated flavones such as 5,7-dihydroxy 3,6,8-trimethoxyflavone and 5,7-dihydroxy 3,6,8,2 ,4 ,5 -hexamethoxyflavone, and some ent-labdane-type diterpene [20][21][22][23]. More recent studies showed the isolation of a diterpene ent-labdene-type: ent-dihydrotumanoic acid (DTA) with antidiarrheal and antinociceptive effects [24][25][26]. However, even when this plant is used in the treatment of some skin problems, there are no studies about the relation between the isolated compounds and these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the compounds isolated from G. glutinosum are methoxylated flavones such as 5,7-dihydroxy 3,6,8-trimethoxyflavone and 5,7-dihydroxy 3,6,8,2 ,4 ,5 -hexamethoxyflavone, and some ent-labdane-type diterpene [20][21][22][23]. More recent studies showed the isolation of a diterpene ent-labdene-type: ent-dihydrotumanoic acid (DTA) with antidiarrheal and antinociceptive effects [24][25][26]. However, even when this plant is used in the treatment of some skin problems, there are no studies about the relation between the isolated compounds and these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts or plant‐derived compounds also exert similar or improved analgesic effects as compared to currently used analgesics, but with less adverse effects [Zapata‐Morales et al,; González‐Chávez et al, ]. Among the compounds currently used as analgesics that were obtained from plant origin are: the alkaloid morphine, isolated from Papaver somniferum L (Papaveraceae), tetrahydrocannabinols isolated from Cannabis sativa L (CannabaceaeMartinov), capsaicin obtained from Capsicum annuum L (Solanaceae) and Capsicum chinense Jacq (Solanaceae), salicilin isolated from Salix alba L (Salicaceae) and rutin, a glycoside flavonoid obtained from Ruta graveolens and other medicinal plants [Calixto, ; Sofic et al, ; Hamad, ].…”
Section: Introductionmentioning
confidence: 99%